2007
DOI: 10.1164/rccm.200609-1331oc
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Factors and Asthma among Health Care Professionals

Abstract: Rationale: Recent U.S. data suggest an increased risk of work-related asthma among health care workers, yet only a few specific determinants have been elucidated. Objectives: To evaluate associations of asthma prevalence with occupational exposures in a cross-sectional survey of health care professionals. Methods: A detailed questionnaire was mailed to a random sample (n ϭ 5,600) of all Texas physicians, nurses, respiratory therapists, and occupational therapists with active licenses in 2003. Information on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
174
3
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(189 citation statements)
references
References 42 publications
11
174
3
1
Order By: Relevance
“…These were also found in some previous studies in America, Britain and Nigeria. (Rosenman et al, 2003, Medina-Ramon et al, 2003, Bello et al, 2009, Imperial College London, 2013, Zock, 2005, Delcos et al, 2006, Orji et al, 2002 The skin lesions may have resulted from insect bite to which these workers are exposed to especially when they are on night shifts while the asthmatic symptoms are due their exposure to dusty particles while doing their work. Other health problems found in this study which were not reported in previous studies include eye problems, burns and upper respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were also found in some previous studies in America, Britain and Nigeria. (Rosenman et al, 2003, Medina-Ramon et al, 2003, Bello et al, 2009, Imperial College London, 2013, Zock, 2005, Delcos et al, 2006, Orji et al, 2002 The skin lesions may have resulted from insect bite to which these workers are exposed to especially when they are on night shifts while the asthmatic symptoms are due their exposure to dusty particles while doing their work. Other health problems found in this study which were not reported in previous studies include eye problems, burns and upper respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…(Lucas and Gilles, 2004, Unge et al, 2007, Tinubu et al, 2010, Omokhodion et al, 2000, Bello et al, 2009) Furthermore, they may also be faced with occupational diseases like Hepatitis B infection, HIV/AIDS and other infections to which other health workers are prone while doing their job. (Imperial College London, 2013, Zock, 2005, Delcos et al, 2006 Skin disorders like dermatitis and psychosomatic disorders have also been reported among hospital cleaners. (Amosu et al, 2011, Medina-Ramon et al, 2005 In many of the tertiary health facilities in Nigeria cleaning works are contracted to cleaning companies which in turn employ the cleaners to work for them.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed analysis in this population showed that reporting bias could not be discarded; individuals with any respiratory problems at baseline were more likely to report inhalation incidents 9 years later (41). Cross-sectional studies also found that asthmatics more often had a history of single high exposure to irritant cleaning products than healthy controls (42)(43)(44). A population-based study in Northern Europe documented an increased asthma risk in men with a history of accidental peak exposure to irritants (45).…”
Section: Epidemiological Evidence For Irritant-induced Asthmamentioning
confidence: 94%
“…Several authors have reported an increase in respiratory morbidity in respiratory therapists (RTs) after they enter the profession. [1][2][3][4] RTs are exposed to infectious and other aerosols while performing their daily tasks. A few years ago the severe acute respiratory syndrome (SARS) epidemic, and more recently the influenza H1N1 epidemic, brought renewed attention to the risk incurred by healthcare providers participating in droplet/aerosol generating procedures.…”
mentioning
confidence: 99%
“…3 More recently, Delclos et al gained more insight into possible causes for this increased pulmonary morbidity. 4 They surveyed a group of physicians, nurses, occupational therapists, and RTs and found that the diagnosis of asthma after entering the profession was associated with some activities such as cleaning medical instruments (OR 2.22, 95% CI 1.34 -3.67) and administration of aerosolized medications (OR 1.72, 95% CI 1.05-2.83). Their questionnaire also inquired about bronchial hyper-responsiveness related symptoms (trouble breathing, wheezing, and/or attacks of shortness of breath, nocturnal cough, and/or chest tightness in the previous 12 months, and current allergic symptoms), and they found an association with general cleaning (OR 1.63, 95% CI 1.21-2.19) and aerosolized medication administration (OR 1.40, 95% CI 1.06 -1.84).…”
mentioning
confidence: 99%